Scanning aerial photos using a non-professional scanner - Ruzgienė, Birutė; Bagdžiūnaitė, Renata; Ruginytė, Vilma (Geodesy and Cartography, 2012)
For scanning analog aerial photographs, digital photogrammetry requires specific and expensive photogrammetric scanners. However, we only have a simple A4 format scanner useful for solving some special photogrammetric tasks applied for analyzing the possibilities of scanning photographic material. The paper investigates the peculiarities of scanning analog aerial photos using the scanner processing pictures smaller than an A4 format. The achieved results are compared with digital data obtained using a professional photogrammetric scanner. Experimental photogrammetric measurements have showed that the results of aerial photographs scanned by a nonprofessional scanner satisfy accuracy requirements for topographic mapping at a scale of 1:5000.